The Prevalence Of Enamel Defects Among The Students Of Secondary School (Age 14-17) In Baghdad/Alrosafa (Mustansiria Dental Journal, 2022)
Aim of the study: To study the occurrence of enamel defects, the most common type and what gender is more affected on the students at the secondary school in Baghdad-Alrosafa. Materials and methods: Eight hundred and fifty students in the secondary school in Baghdad-Alrosafa were included in this study without any systemic disease with a 425 male and 425 female aging from 14 to 17 years old. A diagnostic instrument probe, mirror, gloves and tweezer were used. All students were examined clinically for the presence of enamel defect like enamel fluorosis, amelogenesis imperfecta, enamel erosion, abrasion and attrition. T-test was used for statistical analysis.Results: Results of the current study showed a high percentage of enamel defect occurring in females than in males and a high significant difference recorded at 17 years old in enamel fluorosis with an enamel attrition recording a higher percentage than other anomalies.Conclusion: conclusion of study is that the enamel defect occurs in females more than males and molar teeth have a higher prevalence than other teeth. Attrition recorded a higher percentage than other defects followed by enamel fluorosis and the lower one is amelogenesis imperfacta.